Environmental Communication of Gerakan Ciliwung Bersih for Downstream Communities - Hidayaturahmi; Djuara P. Lubis; Soeryo Adiwibowo; Hariadi Kartodihardjo (West Science Interdisciplinary Studies, 2023)
A social movement is becoming a phenomenon along with development. Most of the social movements relate to environmental issues. River management issues among downstream communities have been increasingly raised as the problems of the river arise. This study aims to identify the social movement of downstream communities for the Ciliwung River and to analyze the communication development model of Gerakan Ciliwung Bersih (GCB) for downstream Ciliwung communities. This study used mixed methods, conducting a survey supported by interviews and observation. The results of the study found that the downstream communities have a different focus on Ciliwung social movement. It depends on the characteristics of the geography and their communities. Secondly, the communication development model of downstream communities mostly focuses on networking development as this influence most public participation in environmental actions. The study recommends collaboration between downstream and upstream communities as the issues of the Ciliwung River cannot be overcome partially between upstream and downstream areas. Finally, networking development as the communication model of the communities has to be combined with the city, capacity development, and organizing communities.